Facilitating bilateral investments between India and Germany: The role of negotiations and reforms - Tanu M. Goyal; Ramneet Goswami; Tincy Sara Solomon (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Germany is a large source country for investment and technology transfer into India and Indian investments in Germany are also growing overtime. The two countries have investment complementarities and, therefore, there is scope to enhance bilateral investments flows. However, there are many market access and operational restrictions, which impact the flow of bilateral investments. In this context, this paper aims to highlight the barriers to investment flows between India and Germany and suggest measures to address these barriers through bilateral trade negotiations and domestic reforms. The paper found that policy uncertainty, rigid regulations and differences in technical and product standards are key barriers to bilateral investment flows between India and Germany. In addition, there are cultural and language barriers and lack of knowledge about the present policies and incentives in the two countries. Investment flows can be facilitated through inter-government agreements as they offer operational certainty and comprehensive trade agreements, which ensure a more liberal and predictable investment regime for the trading partners. The paper suggests that while some of the barriers can be addressed through domestic reforms and trade negotiations, there is also a need to enhance inter-government cooperation, government industry interactions and promote knowledge sharing between the two countries to facilitate investment flows.
Keywords: F15; F21; F51; F53; 330; Investments; India; Germany; International Agreements; Negotiations; Domestic Reforms